Role of Dexamethasone at the Surgical Site in The Control of Pain and Oedema in Management of Bilateral Mandibular Fractures Osteosynthesis Using the Split-Mouth Technique: Dexamethasone and Oedema in Bilateral Mandibular Fractures Osteosynthesis - Pervaiz , Benish; Ashraf, Rutaba; Ain, Noor Ul; Shar, Mor Khan; Uddin, Haseeb; Farooq, Muhammad Umar (Pakistan Journal of Health Sciences, 2025)
Osteosynthesis is a widely used technique for the treatment of fractures, ensuring stability in the healing process. This might cause postoperative pain, edema, trismus, infection, and reduced jaw mobility. Objectives: To assess the effectiveness of Dexamethasone in alleviating pain and oedema at the surgical site in patients undergoing bilateral mandibular fracture osteosynthesis using the split-mouth technique. Methods: A quasi-experimental study was conducted at the Pakistan Institute of Medical Sciences from 11th October 2023 to 10th August 2024, enrolling 30 participants with bilateral mandibular fractures. They were divided into two groups using the split-mouth technique, with 30 surgical sites in each group. Using a table of random numbers, surgical sites were assigned to Group A (study group), in which submucosal dexamethasone was administered after closure of the incision site, and Group B (control group), which did not receive submucosal dexamethasone. Postoperative pain and edema were evaluated at 24 hours, 72 hours, and one week postoperatively. Results: The mean age of the participants was 25.77 ± 8.274, with 73.3% being male. Group A experienced slightly reduced pain than group B (p s 0.005). After 24 hours and 1 week postoperatively, there were statistically significant differences in postoperative oedema among the two groups (p≤0.05), but not at 72 hours (p>0.05). Conclusions: It was concluded that dexamethasone can be used as an adjunct to improve postoperative outcomes in patients with mandibular fractures by decreasing pain and oedema.